Spinning in circles: poverty alleviation ventures in Larimer County, Colorado - Distaso, Cheryl Alane, author; Bundy-Fazioli, Kim, advisor; Bubar, Roe, committee member; Valdez, Norberto, committee member (Colorado State University. Libraries, 2014)
Weaving together grounded theory and autoethnography as methodologies, this thesis interrogates two companion antipoverty initiatives in Larimer County, Colorado. The initiatives studied were Bridges out of Poverty and the Circles Campaign, during the years 2012 and 2013, when they were being piloted locally by funding provided by Bohemian Foundation. Data used in the study include website materials, YouTube videos, notes gathered at public meetings, autoethnographic memos, and artifacts such as tax forms, reports, and other public documents. This study concludes that the initiatives have no reliable efficacy data, reinforce stereotypes, and do not examine root causes of poverty. It is argued that the initiatives are ineffective and dangerous, as they engage in victim blaming and offer the false illusion that poverty is being addressed in our community. Recommendations for the implementation of effective poverty alleviation approaches are given.